2017
DOI: 10.1038/srep41255
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of genes related to immune signaling and detoxification in Apis mellifera by an inhibitor of histone deacetylation

Abstract: The western honeybee (Apis mellifera) is essential for the global economy due to its important role in ecosystems and agriculture as a pollinator of numerous flowering plants and crops. Pesticide abuse has greatly impacted honeybees and caused tremendous loss of honeybee colonies worldwide. The reasons for colony loss remain unclear, but involvement of pesticides and pathogen-pesticide interactions has been hypothesized. Histone deacetylase inhibitors (HDACis) inhibit the activity of histone acetylase, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 59 publications
1
51
0
4
Order By: Relevance
“…Sodium butyrate is an HDACi that inhibits the deacetylation of the histone core and results in increased gene expression (Hu et al ., ). Here, we used western blotting to test whether this is true in the heads of the bees.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Sodium butyrate is an HDACi that inhibits the deacetylation of the histone core and results in increased gene expression (Hu et al ., ). Here, we used western blotting to test whether this is true in the heads of the bees.…”
Section: Resultsmentioning
confidence: 97%
“…A, B, Lane 2). Previous studies demonstrated that sodium butyrate at 10 mM does not induce apoptosis (Hu et al ., ; although there is evidence suggesting otherwise at higher concentrations). Based on these results, we exposed bees to 10 mM sodium butyrate for 7 days with the goal of increasing the acetylation of H3 and H4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no ROS accumulation was detected in NaB‐treated seeds, it is reasonable to hypothesize that the overall up‐regulation of antioxidant genes might be due to increased histone acetylation rather than oxidative stress. NaB has been reported to improve cell viability through the up‐regulation of antioxidant genes in insects (Hu et al, ) and human (Tang et al, ). It is worth noting that oxidative injury, such as enhanced DNA damage, as well as exposure to NaB can induce ER (endoplasmic reticulum) stress (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that insecticide sensitivity in insects might be regulated by epigenetic mechanisms involving DNA methylation (Oppold et al, 2015) and chromatin modifications (Hu et al, 2017;Scientific Reports 7:41255 Involves any process to change state and activity of molecular processes. The herewith associated gene "transient receptor potential channel pyrexia" is responsive to high temperatures and involved in protection and tolerance from high temperature stress in D. melanogaster (Lee et al, 2005).…”
Section: Methylationmentioning
confidence: 99%